Transmission characteristics of a two dimensional antiscatter grid prototype for CBCT. Issue 8 (16th June 2017) - Altunbas, Cem; Kavanagh, Brian; Alexeev, Timur; Miften, Moyed
Abstract : Aim: High fraction of scattered radiation in cone‐beam CT (CBCT) imaging degrades CT number accuracy and visualization of low contrast objects. To suppress scatter in CBCT projections, we developed a focused, two‐dimensional antiscatter grid (2DASG) prototype. In this work, we report on the primary and scatter transmission characteristics of the 2DASG prototype aimed for linac mounted, offset detector geometry CBCT systems in radiation therapy, and compared its performance to a conventional one‐dimensional ASG (1DASG). Methods: The 2DASG is an array of through‐holes separated by 0.1 mm septa that was fabricated from tungsten using additive manufacturing techniques. Through‐holes' focusing geometry was designed for offset detector CBCT in Varian TrueBeam system. Two types of ASGs were evaluated: (a) a conventional 1DASG with a grid ratio of 10, (b) the 2DASG prototype with a grid ratio of 8.2. To assess the scatter suppression performance of both ASGs, Scatter‐to‐primary ratio (SPR) and scatter transmission fraction (Ts) were measured using the beam stop method. Scatter and primary intensities were modulated by varying the phantom thickness between 10 and 40 cm. Additionally, the effect of air gap and bow tie (BT) filter on SPR and Ts were evaluated. Average primary transmission fraction (TP ) and pixel specific primary transmission were also measured for both ASGs. To assess the effect of transmission characteristics on projection image signal‐to‐noise ratio (SNR), SNR improvement factor was calculated. Improvement in contrast to noise ratio (CNR) was demonstrated using a low contrast object. Results: In comparison to 1DASG, 2DASG reduced SPRs by a factor of 3 to 6 across the range of phantom setups investigated. Ts values for 1D and 2DASGs were in the range of 21 to 29%, and 5 to 14% respectively. 2DASG continued to provide lower SPR and Ts at increased air gap and with BT filter. Tp of 1D and 2DASGs were 70.6% and 84.7% respectively. Due to the septal shadow of the 2DASG, its pixel specific primary transmission values varied between 32.5% and 99.1%. With respect to 1DASG, 2DASG provided up to factor of 1.7 more improvement in SNR across the SPR range investigated. Moreover, 2DASG provided improved visualization of low contrast objects with respect to 1DASG and NOASG setups. Conclusions: When compared to a conventional 1DASG, 2DASG prototype provided noticeably lower SPR and Ts values, indicating its superior scatter suppression performance. 2DASG also provided 19% higher average primary transmission that was attributed to the absence of interseptal spacers and optimized grid geometry. Our results indicate that the combined effect of lower scatter and higher primary transmission provided by 2DASG may potentially translate into more accurate CT numbers and improved contrast resolution in CBCT images.